The Role of Community Libraries in Repackaging Scientifically Researched Information for Rural Farming Communities: A Review - Kiwelu, Jackline Estomihi Mayende; Ngulube, Patrick (Evidence Based Library and Information Practice, 2025)
Objective – Scientifically researched information is often found in journal articles, book chapters, and conference papers, which can be technical and challenging for those without training. Repackaging information into a simpler and preferred language can make it easier for undereducated rural communities to access. This narrative review investigates the strategies community libraries can adopt to repackage scientifically researched information for easier access by rural farming communities. This study contributes to the literature gap on research-based information repackaging by community libraries for rural development.Methods – The literature search for this narrative review was conducted across several databases, electronic discovery tools, and individual journal articles. Google Scholar, EBSCOhost, Emerald, AGORA, Scopus, and Wiley collections were searched. Reference lists from various journal articles, book chapters, and conference papers were reviewed to select the desired studies for inclusion in this review.Results – The findings highlight the challenges community libraries face in Africa when repackaging research-based information for farmers, as discussed in relation to those reported in other parts of the world. These challenges include a lack of information and communications technologies (ICT) infrastructure, limited budgets, the absence of relevant policies, low awareness, and inadequate skills among library staff. Additionally, community libraries are scarce in rural areas, and those that exist often lack updated, scientifically researched information. To address these issues, the study proposes strategies such as collaborating, considering community norms and cultures, training community librarians in digital and appropriate repackaging methods, and equipping rural libraries with reliable, research-based information and necessary ICT tools.Conclusions – This study highlights the critical role of information repackaging in enhancing access to scientific farming knowledge for rural communities through community libraries. By translating complex information into user-friendly formats, libraries meet farmers' unique needs effectively. The integration of digital technologies further strengthens this process. The findings extend beyond the African context, as rural libraries worldwide face similar challenges in delivering context-specific knowledge, promoting information literacy, and engaging communities. Thus, the strategies highlighted in this study may be applied globally. Future research should explore the effectiveness of different repackaging strategies, the role of digital tools in various contexts, and the training needs of community librarians to optimize information delivery.